2020
DOI: 10.3390/rs12050786
|View full text |Cite
|
Sign up to set email alerts
|

Using MODIS LAI Data to Monitor Spatio-Temporal Changes of Winter Wheat Phenology in Response to Climate Warming

Abstract: Understanding spatio-temporal changes in winter wheat (Triticum aestivum L) phenology and its response to temperature will be vital for adapting to climate change in the coming years. For this purpose, the heading date (HD), maturity date (MD), and length of the reproductive growth period (LRGP) were detected from the remotely sensed leaf area index (LAI) data by a threshold-based method during the harvest year 2003 to 2018 across the North China Plain. The results show that there was high spatial heterogeneit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Furthermore, the combination of climatic (i.e. temperature, growing degree days) and satellite data has resulted in an adequate approach for estimating phenology, as previous studies have suggested [58,59], and wheat grain yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the combination of climatic (i.e. temperature, growing degree days) and satellite data has resulted in an adequate approach for estimating phenology, as previous studies have suggested [58,59], and wheat grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that the results here obtained showed that focusing on phenology for grain yield estimation is now possible using Sentinel-2 imagery and not only applicable with ground and proximal sensing. Furthermore, the combination of climatic (i.e., temperature, growing degree days) and satellite data has resulted in an adequate approach for estimating phenology, as previous studies have suggested [58,59], and wheat grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…eaf area index (LAI) [1] and the fraction of photosynthetically active radiation (FPAR) (0.4-0.7 μm) absorbed by vegetation [2], characterizing structure and functioning and energy absorption capacity of vegetation canopy, are two important parameters of many ecological, agronomic, climate and land surface process models [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…These products have been widely used to monitor vegetation phenology, capture impacts of climate change and natural disaster etc. [5,11,12]. However, because of the long revisit time and cloud contamination, all of these products from low earth orbiting (LEO) sensors observations are often so temporally and spatially incomplete that the data usability is greatly reduced [13].…”
Section: Introductionmentioning
confidence: 99%
“…Leaf area index (LAI) is defined as one half the total green leaf area per unit horizontal ground surface area (Chen and Black 1992), is one of the basic climate variables defined by the Global Climate Observing System (GCOS). LAI determines the effective cross-section of the interaction between the earth and atmosphere and is an important biophysical parameter in vegetation growth monitoring (Jin et al 2016;Fang et al 2019b;Song et al 2020), global climate change (Martin et al 2016;Tao, Chen, and Fu 2020) and land surface process models (Chaney, Metcalfe, and Wood 2016;Xie et al 2019). In order to run largescale ecosystem models, we need regional and even global LAI data (Myneni et al 2002).…”
Section: Introductionmentioning
confidence: 99%